Ecommerce Platform for Furniture Store - F, Piyoshila; Jeyaseelan S.; O.S., Udumullarachchi; G.P.A.H.R., Perera; Silva, D I De; Cooray, Dulanji (International Journal of Engineering and Management Research, 2022)
In recent years, people’s acceptance of online shopping has increased markedly with the gradual maturing of e-commerce. This paper aims to propose an ecommerce platform for furniture stores that suits small and medium businesses to expand choice and convenience, allowing customers to buy from a wide array of products with the click of a button. Although there are many existing ecommerce systems in the market, our proposed system stands out for its user experience. This proposed system focuses mainly on four main functions: product management, order management, order-review management, and user management. The current research has been undertaken to walk you through the literature view, methodology, functional overview of the proposed ecommerce system, and discussion. The study further examines the key variables imperative for the success of the proposed system. The findings of this study afford practical implications for the improvement of the online shopping experience of consumers for furniture companies.